1706. IgM Monoclonal Antibodies Targeting Peptidoglycan May Provide Therapeutic Strategies against Antimicrobial Resistant Bacteria. (15th December 2022) - Kroscher, Kellie; Rikhi, Nimisha; Muema, Kevin; Schuman, Richard F; Assiaw-Dufu, Aba; Sei, Clara J; Fischer, Gerald W
Abstract: Background: Antimicrobial resistance (AMR) poses a substantial global threat to human health and development. In addition to death and disability, the cost of AMR to the global economy is significant. Prolonged illness results in longer hospital stays and the need for more expensive medicines and financial challenges for those impacted. Therapeutics such as monoclonal antibodies (mAbs) may offer prevention and control measures against microbial infections without the use of antibiotics. In this study, we developed human antibodies (serum and mAbs) against components of staphylococcus aureus (SA) and Mycobacterium tuberculosis (MTB) and evaluated their capabilities. Methods: Humanized DRAGA mice were immunized with 20μg of a combination vaccine comprised of Ultrapure peptidoglycan (PGN, derived from SA) and TB Pep01 peptide (targeting MTB HSP16.3), formulated with AddaVax™ adjuvant. Serum antibody responses to PGN, TB Pep01, and various whole bacteria were analyzed using ELISA. Mice with high antisera titers was selected for hybridoma production. Hybridomas were screened for binding to PGN, TB Pep01, and whole bacteria using ELISA and high producing clones were selected for monoclonal antibody development. Results: Early and enhanced serum IgM responses to PGN were observed by Day-21, while IgG responses to PGN were detected at Day-35. Antisera binding to TB Pep01 was demonstrated, albeit lower than PGN. In addition, antisera recognition of whole bacteria was shown. Hybridoma clones (IgM) targeting PGN were identified for monoclonal antibody production. Conclusion: Hybridomas developed in humanized DRAGA mice immunized with PGN and TBPep01 bound to the immunogens and showed broad recognition of various microbes. Ongoing studies to evaluate mAb functional activity against various microbes to include mycobacteria and staphylococci are in progress. IgM mAbs that recognize and whole bacteria, and opsonize and kill multiple bacterial strains, may provide an effective antimicrobial strategy for treatment of drug resistant bacterial infections. Disclosures: All Authors : No reported disclosures.